2015
DOI: 10.3892/ol.2015.3935
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein inhibits the migration and invasion of colorectal cancer cells via suppression of the AKT signaling pathway

Abstract: Abstract. The anticancer effect of baicalein has been known for a number of years. However, its anti-metastatic effect and associated mechanisms in colorectal cancer (CRC) remain unclear. The present study investigated the hypothesis that treatment with baicalein may inhibit the proliferation, motility and invasion of human CRC cell lines via regulation of the protein kinase B (AKT) signaling pathway. Baicalein was demonstrated to significantly inhibit the migration and invasion of CRC cells (P=0.01). Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(75 citation statements)
references
References 26 publications
1
74
0
Order By: Relevance
“…Previous studies demonstrated that baicalein could exert its anti-tumor effect through modulating the PI3K/AKT signaling pathway in several cancer types [26-28]. To explore the effect of baicalein on PI3K/AKT pathway, the phosphorylation level of AKT at Thr308 and Ser473 in Bel-7402 cells treated with 0, 40 and 80 µM baicalein for 24 h was detected by western blotting, we found the phosphorylation level of AKT at both Thr308 and Ser473 were significantly decreased by baicalein treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated that baicalein could exert its anti-tumor effect through modulating the PI3K/AKT signaling pathway in several cancer types [26-28]. To explore the effect of baicalein on PI3K/AKT pathway, the phosphorylation level of AKT at Thr308 and Ser473 in Bel-7402 cells treated with 0, 40 and 80 µM baicalein for 24 h was detected by western blotting, we found the phosphorylation level of AKT at both Thr308 and Ser473 were significantly decreased by baicalein treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Both MMP-2 and MMP-9 are crucial proteases for the invasion and migration of CRC cells. Treatment of CRC cells with baicalein significantly inhibited cellular migration and invasion by suppressing the activities of MMP-2 and MMP-9 (via inhibition of the Akt pathway) [12]. Another group looked at the effect of baicalein on DLD-1 cells (colorectal adenocarcinoma cells) using proteomic analysis.…”
Section: Baicalein and Colorectal Cancermentioning
confidence: 99%
“…Baicalein is a flavone and an active ingredient in the traditional herb, Huang Qin. There is an accumulating amount of evidence that demonstrates baicalein’s role in treating and preventing various types of cancer [9,10,11,12,13,14,15]. In this review, we explored its chemical structure, properties, and possible biological mechanisms through which it acts.…”
Section: Introductionmentioning
confidence: 99%
“…Our study also showed that downregulation of CPEB4 increased level of cellular ROS, which may result in decreasing p‐Akt levels. Akt phosphorylation signal may contribute to cancer cells functioning, such as viability (Tang et al, ), proliferation (Zhou et al, ), invasion (Rui et al, ) and migration (Wang et al, ; Zhou et al, ). In the present study, our data indicated PI3 K/Akt inhibitor, LY294002, which effectively suppressed siCPEB4 suppresses cell migration and invasion of NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%